North-South Migration and Urban Poverty in Ghana: The Case of Greater Accra. - Yahaya, A. (University of Ghana, 2019)
More than half the world’s population in recent times lives in cities. Urban growth is over 90 percent in developing countries, with an annual increase of about 70 million migrants migrating from rural areas to urban areas. The number of urban drawlers is expected to increase in the world’s two poorest regions (South Asia and Sub-Saharan Africa) in the next two decades. The study aims at the relationship between rural-urban migration and urban poverty in Ghana with a focus on some areas in Accra. The researcher administered questionnaires, interview guide, visually observed and took notes on the field. Information was collected from rural migrants of the sampled population. Also, information was obtained from two resource persons in the subject areas. Results depict that the youth migrate more; lack of employment opportunities as one of the main motivations for migrating; migrating claim to be doing better than living in the north.
MPA.
Keywords: North-South Migration; Urban Poverty; Greater Accra